Os desdobramentos do feminino na poesia de Florbela Espanca - Nascimento, Michelle Vasconcelos Oliveira do (2011)
This work has the purpose to analyze the female images unrolled at the Florbela Espanca (1894 -1930) poetry of her three books published, Livro de Mágoas (1919), Livro de Sóror Saudade (1923) e Charneca em Flor (1931, posthumous), showing how the female mythic constituents Eve and Lilith advance among the books, delineating the female image which culminates to the female poet image, free of moral conventions and social principles in the beginning of 20th century. For this exam, we will apply the Imaginary criticism, and realize a short explanation about mythic archetypes theories from C.G. Jung, Mircea Eliade, E. Meletínki and Gilbert Durand, theories that will lead us to make the connection between the mythic constituents and Nietzsche tragic constituents, from which we will explain how these female mythic images associated to reason and unreason mythic constituents, unrolled at the Florbela poetry, also reveal the tragic esthetic at her work